Case Report: DOCK8 Deficiency Without Hyper-IgE in a Child With a Large Deletion - Venegas-Montoya, Edna; Staines-Boone, Aidé Tamara; Sánchez-Sánchez, Luz María; García-Campos, Jorge Alberto; Córdova-Gurrola, Rubén Antonio; Salazar-Galvez, Yuridia; Múzquiz-Zermeño, David; González-Serrano, María Edith; Lugo Reyes, Saul O. (Frontiers in Pediatrics, 2021)
Autosomal recessive (AR) DOCK8 deficiency is a well-known actinopathy, a combined primary immune deficiency with impaired actin polymerization that results in altered cell mobility and immune synapse. DOCK8-deficient patients present early in life with eczema, viral cutaneous infections, chronic mucocutaneous candidiasis, bacterial pneumonia, and abscesses, together with eosinophilia, thrombocytosis, lymphopenia, and variable dysgammaglobulinemia that usually includes Hyper-IgE. In fact, before its genetic etiology was known, patients were described as having a form of Hyper-IgE syndrome, a name now deprecated in favor of genetic defects. We describe a school-age male patient with a clinical picture suggestive of DOCK8 deficiency, except for high serum IgE or a family history: early onset, failure to thrive, eczema, warts, condyloma, bronchiolitis, pneumonia, recurrent otitis media, bronchiectasis, candidiasis, leukocytosis, eosinophilia, high IgA, low IgG, and low CD4+ T cells. We were able to confirm the diagnosis through protein expression and whole-exome sequencing. We review the clinical, laboratory, and genetic features of 200 DOCK8-deficient patients; at least 4 other patients have had no elevated IgE, and about 40% do not have Hyper-IgE (above 1,000 IU/mL). Despite this, the constellation of signs, symptoms, and findings allow the suspicion of DOCK8 deficiency and other actinopathies.